Practical research : planning and design - Leedy, Paul D.; Ormrod, Jeanne Ellis (Uttar Pradesh, India : Pearson India Education Services, 2020)
Practical Research: Planning and Design is a do-it-yourself, how-to manual for planning and conducting research. Suitable for a wide variety of courses in basic research methodology, the book uses a conversational tone, step-by-step instructions, and practical suggestions to guide the reader from the selection of a problem to the preparation of a completed report.
Nature and tools of research -- Problem : the heart of the research process -- Review of the related literature -- Planning your research project -- Writing the research proposal -- Descriptive research -- Experimental, quasi-experimental, and ex post facto designs -- Qualitative research methods -- Mixed-method designs -- Action research and participatory designs -- Analyzing quantitative data -- Analyzing qualitative and mixed-methods data -- Planning and preparing a final research report -- Appendix A. Using a spreadsheet : Microsoft Excel -- Appendix B. Using SPSS.
Includes bibliographical references and index.
Keywords: RESEARCH METHODOLOGY